IDENTIFIKASI TUMBUHAN MANGROVE DAN PEMANFAATANNYA DI PULAU ARU PROVINSI MALUKU - Andi Nur Samsi; Muhammad Sri Yusal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
This study aims to determine the types of mangrove plants and their benefits to the ecosystem in the Aru Islands (Kalar-Kalar Village) from August to October 2020. The method used in this study is the survey method. Sampling in the field was carried out using exploration, interview, and documentation techniques. The results of this study obtained 10 different types of mangroves, namely: Achantus ebracthus, Achantus ilicifolius, Acrostichum aereum, Aegiceras floridum, Avicennia eucalyptifolia, Avicennia lanata, Bruguiera gymnorrhiza, Lumnitzera littorea, Xylocarpus granatum, and Nypa fruticans. Mangrove plants are used as medicine, vegetables, firewood, building materials, and cigarette paper materials. The parts used are the leaves, stems, and fruit.